Gluphisia irene, a new species (Lepidoptera, Notodontidae) from China and some taxonomical remarks about the palaearctic Gluphisia Boisduval, 1828 - Saldaitis, Aidas; Pekarsky, Oleg (Zootaxa, 2016)
A new species of Gluphisia irene sp. n., from China’s Sichuan Province is described. The new species differs in appearance and genitalia from its closest relatives, Gluphisia crenata (Esper, 1785), Gluphisia tristis Gaede, 1933 stat. n. and Gluphisia meridionalis Kiriakoff, 1963 stat. n. described from Europe and China, respectively.